1983
DOI: 10.1093/carcin/4.9.1179
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity testing of steroids obtained from bile acids and cholesterol

Abstract: Twenty bile acid or cholesterol derivatives were tested for mutagenicity by the Ames spot test procedure against five Salmonella typhimurium strains in the presence and absence of rat liver microsomes. No strong mutagens were identified, but four of the compounds increased the number of revertant colonies observed. Three of these compounds were selected for dose response experiments using the Ames plate incorporation assay procedure with strain TA 1538. No positive results were obtained. These results suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The genetic toxicity studies in bacteria and cts on male rodents reported here were negative, with the exception of an equivocal response in the peripheral blood micronucleus test in the high dose female mice exposed to androstenedione for 14 weeks. These results are in agreement with other published genetic toxicity test results (McKillop et al, 1983). …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The genetic toxicity studies in bacteria and cts on male rodents reported here were negative, with the exception of an equivocal response in the peripheral blood micronucleus test in the high dose female mice exposed to androstenedione for 14 weeks. These results are in agreement with other published genetic toxicity test results (McKillop et al, 1983). …”
Section: Discussionsupporting
confidence: 94%
“…Mutagenicity was not seen with androstenedione (500 μg/disc) in a spot test using S. typhimurium strain TA1538, with and without induced rat liver S9 enzymes (McKillop et al, 1983). A more potent androgen, testosterone (500 μg/plate), was negative in S. typhimurium strains TA100, TA1535, and TA1538, with and without rat liver S9 (Ingerowski et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Several bacterial studies have revealed the mutagenic effects of BA and their metabolites. Through single‐gel electrophoresis assays, Ames tests, fluctuation assays, and reversion assays in various Salmonella strains, research groups have identified the formation of DSBs, single‐strand DNA breaks, abasic sites, frameshift mutations, base‐pair substitutions, and point mutations in response to bile‐salt exposure . Results have shown that frameshift mutations (−1) were a result of the adaptive SOS response to the stressor BA, and point mutations were largely comprised of nucleotide substitutions (GC to AT transitions), suggesting that exposure to BA salts can result in oxidative DNA damage …”
Section: Dna Damagementioning
confidence: 99%
“…However, although the epidemiological evidence favors a role for the NDC, unsaturated bile acids of the type expected have yet to be isolated and identified in feces. Furthermore, McKillop and colleagues (4) have shown that a range of unsaturated steroids derived from bile acids and cholesterol are not mutagenic in the Ames salmonella mutagenicity assay.…”
Section: Introductionmentioning
confidence: 99%